Bradykinin-Mediated Angioedema Induced by Commonly Used Cardiovascular Drugs - Janina Hahn; Jens Greve; Murat Bas; Georg Kojda (Drugs and Drug Candidates, 2023)
ACE inhibitors, sartans, and sacubitril are among the most important drugs for the prevention of cardiovascular mortality and morbidity. At the same time, they are known to cause non-allergic bradykinin-mediated angioedema, a potentially fatal swelling of the mucosa and/or submucosa and deeper skin without signs of urticaria or pruritus, occurring mainly in the head and neck region. In contrast with hereditary angioedema, which is also mediated by bradykinin, angioedema triggered by these drugs is by far the most common subtype of non-allergic angioedema. The molecular mechanisms underlying this type of angioedema, which are discussed here, are not yet sufficiently understood. There are a number of approved drugs for the prevention and treatment of acute attacks of hereditary angioedema. These include inhibitors of bradykinin synthesis that act as kallkrein inhibitors, such as the parenterally applied plasma pool, and recombinant C1 esterase inhibitor, ecallantide, lanadelumab, and the orally available berotralstat, as well as the bradykinin receptor type 2 antagonist icatibant. In contrast, no diagnostic tools, guidelines, or treatments have yet been approved for the diagnosis and treatment of acute non-allergic drug-induced angioedema, although it is more common and can take life-threatening courses. Approved specific drugs and a structured diagnostic workflow are needed for this emergency diagnosis.